Dari Siswa untuk Siswa Keberhasilan Konseling Teman Sebaya di SMK Muhammadiyah 4 Surakarta - Hamidah, Rista Nur; Santiningtyas, Widya Yuli; Kristanto, Ichsan (Universitas Negeri Jakarta, 2024)
The community engagement conducted at SMK Muhammadiyah 4 Surakarta aimed to enhance students' understanding of peer counseling. Through a series of activities, including lectures, Focus Group Discussions (FGDs), and peer counseling practice, the results of this engagement showed an improvement in students' understanding of the role and skills required as peer counselors. Pretest and posttest results demonstrated significant development in students' comprehension of peer counseling. Furthermore, FGDs provided a platform for students to share experiences and discuss relevant issues, while peer counseling practice offered direct experience in being both counselors and clients. Recommendations for further development include increased involvement of schools and parents, as well as the adoption of technology for monitoring and evaluating the progress of activities.